1012 A Close Loop Audit of Acute Food Bolus Obstruction at a District General Hospital. (19th August 2022) - Thakkar, R; Lowe, E; Dennis, S; Islam, M
Abstract: Aim: The British Society of Gastroenterology (BSG) recommends biopsies from two different regions in the oesophagus. A close loop audit was undertaken to assess performance at a district general hospital, against these guidelines and following newly agreed trust guidelines after the first audit cycle of a follow up OGD within 6 weeks of the presentation. Method: Data was collected of patients admitted with a food bolus over the first cycle (March2019 to February 2021) and the second cycle (1/10/21 to 14/10/21). Exclusion criteria were age of less than 18 and sharp food bolus. Results: 69 patients were identified. Average age was 60 years. There were 67% male patients and 33% female. 20% of patients underwent a follow up OGD in the first cycle and 45%underwent a follow up OGD within six weeks. 7% had two regions biopsy in the first cycle and21% in the second cycle. Average OGD follow up time was 92 days in the first cycle and 59days in the second cycle. Commonest findings on histology results were eosinophilic oesophagitis and Barrett's oesophagus (22% each), GORD (15%) and carcinoma (7%). Discussion: Food bolus obstruction indicates the presence of pathology of the oesophagus and should be investigated as so, even despite spontaneous recovery from the acute event. Number of patients undergoing OGD within six weeks and a two regions biopsy improved through this audit by implementing the new trust guidelines.